Papel de los protozoos ciliados ruminales en la síntesis de ácido linoleico conjugado. Revisión (2012)
ABSTRACT: Traditionally, ruminal ciliate protozoa have been studied with respect to the metabolism of dietary nutrients. Their role has focused on their predatory behavior, the paradigm of its retention in the rumen, and its apparent limited flow to the duodenum. On the other hand, Conjugated Linoleic Acid (CLA) and Vaccenic Acid (VA) are important because of their nutritional value. This review aims to characterize the biological alternatives used by rumen ciliate protozoa for the production of CLA, highlighting three aspects: 1) rumen protozoa are involved only in the initial stage of biohydrogenation to produce CLA isomers, 2) desaturation by protozoa has not been reported, while endogen synthesis by desaturation of VA in mammary glands and fatty tissues has been demonstrated as the main route of CLA in ruminants, 3) even though incorporation of VA and cis9, trans11-CLA in protozoa structure is related with CLA production, this is only important when protozoa flow from rumen to duodenum, producing 30 to 43% of CLA and a 40% of VA, respectively. It is concluded that rumen protozoa are fundamental in the lipid metabolism of ruminants.